Uniportal VATS lymphadenectomy - Martin-Ucar, Antonio E.; Socci, Laura (Video-Assisted Thoracic Surgery, 2017)
Lymphadenectomy is an important part of the surgical treatment for lung malignancies. The criticism of limitations in minimally invasive techniques regarding lymphadenectomy has been shown not to be evidenced. We describe the techniques of mediastinal lymphadenectomies during the uniportal VATS (uniVATS) approach with video attachments.